Néstor Tomás Auza, La misión Sarmiento en Chile y Perú y el Congreso Americano, 1864-1865, Buenos Aires, Librería Editorial Histórica, Emilio J. Perrot, 2007, pp. 407. - Rosa, María Fernanda de la (2007)
Fil: Rosa, María Fernanda de la. Investigadora Independiente; Argentina